(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
This research aims to determine if there is any influence on the quality of administration services to the satisfaction of participants in the service of PT. TASPEN Manado Branch and what indicators most affect the quality of the service. Where the administrative service quality variables are measured through four indicators of Zeithaml’s theory of existence, responsiveness, reliability, assurance and certainty, and empathy. This research uses a descriptive quantitative method. The sample in this study was 36 respondents. Data collection techniques used in this research with poll/questionnaire methods and interviews. The results showed that the quality of administration service has a significant positive effect on the satisfaction of participants in PT TASPEN Manado branch. Which means variable quality of administration services is a factor that determines the satisfaction of service participants. The better the level of quality of administration service will be better/higher also the level of customer satisfaction in the office of PT TASPEN Manado Branch and the indicator that most influences the quality of administration services is the indicator of reliability and empathy where both have the total value correlation/r count the most hight than other indicators. Keywords : Quality of service Administration, satisfaction services